Numerical investigation on the combustion and emissions of a kerosene-diesel fueled compression ignition engine assisted by ammonia fumigation. (15th October 2017) - Tay, Kun Lin; Yang, Wenming; Li, Jing; Zhou, Dezhi; Yu, Wenbin; Zhao, Feiyang; Chou, Siaw Kiang; Mohan, Balaji
Highlights: Nitrogen oxide emissions depend on combustion temperature, ammonia quantity and kinetics. Thermo-physical properties of pilot fuel affect engine performance and emissions. An advanced start of injection causes a peak heat-release during late combustion phase. Abstract: As the world faces energy shortages, it is highly desirable to look for alternative fuels that are sustainable and renewable. Ammonia is one such candidate. In this numerical study, ammonia is applied to a diesel engine via fumigation and a pilot fuel is used to ignite the premixed ammonia. Numerical simulations are carried out using the KIVA4-CHEMKIN code in order to better understand the effects of ammonia combustion on engine performance and emissions. It is seen from this study that ammonia reduces carbon monoxide and carbon dioxide emissions as it replaces the carbon-based pilot fuels. Moreover, nitrogen oxide emissions decrease with little ammonia fumigation and increase with high ammonia fumigation. This is due to combustion temperature, ammonia quantity and ammonia-air kinetics. Furthermore, it is interesting to note that as the injection timing is advanced, primary as well as secondary heat-release peaks are observed. The secondary heat-release peak is due to the combustion of residual fuel near the cylinder liner as well as in the crevice region and this is caused by an increase in in-cylinder temperature as injection timing advances.